Human oligodendrocytes in remyelination research. Issue 4 (24th November 2014) - Czepiel, Marcin; Boddeke, Erik; Copray, Sjef
<x xml:space="preserve">Abstract</x> Studies on myelination and oligodendrocyte development are inevitably linked with demyelinating conditions such as multiple sclerosis (MS), leukodystrophies or spinal cord injury (SCI). Chronic loss of myelin, subsequently leading to neurodegeneration, is the ultimate cause of severe and permanent disability. Thus, fast restoration of myelin (remyelination) is essential for circumventing demyelination‐caused pathologies. Implantation of exogenous remyelinating cells has been considered as a potential remyelination strategy. Researchers have examined a variety of cell types endowed with myelin‐forming capacity (oligodendrocytes, Schwann cells, olfactory ensheathing cells etc.) in vitro and in vivo for their potential application as myelin restoring cell grafts. This review gives a summary of studies on the generation and testing of pure suspensions of human oligodendrocytes as a clinically relevant, efficient cellular tool for treating myelin pathology. We start with a brief overview of the current knowledge on the development of human oligodendrocytes from the late stages of embryogenesis up to the early postnatal stage. Insight in the specific extrinsic and intrinsic factors regulating normal oligodendrogenesis is crucial in order to achieve and maintain a sufficient population of engraftable functional oligodendrocytes in vitro. We discuss potential sources of human oligodendrocytes, including novel oligodendrocyte generation strategies employing induced pluripotent stem cells (iPSCs) and direct conversion technology. Finally, we provide a systematic overview of (the outcome of) experimental studies, in which human oligodendrocytes were tested for their (re)myelination capacity and efficiency. GLIA 2015;63:513–530